DIAGNÓSTICO DEL EMPLEO INFORMAL DE LAS PERSONAS QUE FRECUENTAN LAS PROXIMIDADES DEL PARQUE CENTRAL DE LA CIUDAD DE LOJA. - Tandazo Sánchez., Raúl Alcívar (2024)
The present investigation, entitled "Diagnosis of the Informal Employment of People Who Frequent the Proximities of the Central Park of the City of Loja", was carried out by rigorously following all the phases of the research process required for the special degree projects, in accordance with the provisions of the Higher Academic Regime Regulations of the National University of Loja. In this context, the specific objectives set were achieved, which were: to determine the current situation of informal work of people who go to the central park of the city of Loja in search of employment and to prepare a proposal for a solution to the problem of informal work. in the vicinity of the central park of the city of Loja. To develop this diagnosis, it was essential to select appropriate methodologies for robust action research. Consequently, made it possible to identify the public and private actors that influence the problem of unemployment in this sector. Likewise, the logical framework methodology was used, which facilitated the development of the problem tree and the objective tree, providing a comprehensive understanding of the problem and allowing the establishment of an appropriate solution proposal. The results of this research reveal a diverse and predominantly mestizo population in the Central Park of Loja, with significant variations in educational levels and family responsibilities. Labor informality is high, with prevalent temporary contracts and general dissatisfaction with salaries. There is a lack of knowledge about government programs, although the majority are willing to train, preferring online formats.